Averil Cameron, Transitions, A Historian’s Memoir, Studi e Testi Tardoantichi, Profane and Christian Culture in Late Antiquity (Turnhout: Brepols, 2024), pp. 308 - Finn, Richard Damian (New blackfriars, 2025)
Averil Cameron, Transitions, A Historian’s Memoir, Studi e Testi Tardoantichi, Profane and Christian Culture in Late Antiquity (Turnhout: Brepols, 2024), pp. 308. - Volume 106 Issue 6